Implementation of construction waste management and minimization in construction industry of Kedah - Juliana Ayunie Binti Jamaludin (School of Environmental Engineering, University Malaysia Perlis, 2014)
A recent study highlighted fact that waste management in construction industry has been receiving less attention comparison with construction cost and time. Most of the contractors not practicing waste minimization, because they argued that the waste materials have little value and these cause them to dispose the waste in landfills. Hence, the objective of this research are to identify practice of construction waste management in construction industry, identify the disposal method applied at site and factor affecting generation of construction waste and to determine barriers practicing waste management and element to a successful waste management.